Approaches in Islamic Educational Management: A Conceptual Analysis and Its Implications for the Management of Educational Institutions - M. Hanif Satria Budi; Nur Efendi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The management of Islamic educational institutions in the modern era faces complex challenges that require a managerial approach that is not only technically effective, but also aligned with Islamic values and the social context of society. Therefore, a management model that is capable of integrating various approaches comprehensively is needed. This study aims to analyze four main approaches in Islamic educational management, namely the rational approach, the community figure approach, the cultural approach, and the opinion formation approach, as well as to examine their implications for the management of educational institutions. The research problems in this study include the characteristics of each approach and how their synergy can improve the effectiveness of Islamic educational institution management. The method used is qualitative research in the form of a literature study, sourced from relevant books and scientific journals, and analyzed using content analysis techniques. The results of the study show that the rational approach plays a role in creating a structured and data-based management system, while the community figure approach provides social legitimacy through charismatic leadership. The cultural approach functions to strengthen the internalization of Islamic values within the organizational culture, whereas the opinion formation approach contributes to building institutional image and public trust. The integration of these four approaches produces a holistic management model that not only improves organizational efficiency and effectiveness, but also strengthens the competitiveness, adaptability, and sustainability of Islamic educational institutions amid global dynamics.